Mapping your career : the book that can help you find the job you want, and create the career you are meant for - Crisp Editors (Crisp Pub. Menlo ParkUS, 2002)
Provides direction both for students in search of their first job, and for workers who desire a career change. Examines 12 topics including: attitude and attitude adjustment techniques; using professional contacts, as well as the telephone and the Internet in the job search; preparing a resume; interview preparation and techniques; and self-employment.